Perbandingan Kinerja Keuangan pada Bank Woori Saudara Sebelum dan Setelah Merger - Arizal Jaya; Mochamad Edman Syarief; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
This study aims to determine the significant difference between the financial performance of PT Bank Woori Saudara Indonesia 1906, Tbk pre-merger and post-merger. The indicators used in this study are financial ratios consisting of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return On Assets (ROA), and Operating Costs to Operating Income (BOPO) obtained from the annual financial report of PT Bank Woori Saudara Indonesia 1906, Tbk in 2009-2019. The data analysis method used was the non-parametric Wilcoxon signed-rank test. The results showed that there were significant differences in LDR, ROA, and BOPO, while in NPL and CAR there were no significant differences.